Effect of oregano essential on the properties of mango kernel starch films - Sarifuddin, Norshahida; Ahmad A. Shahrim, Nur’Aishah; Azman, K.S (Institute of Physics Publishing, 2018)
The mango kernel starch (MKS) - glycerol (GLY) films were prepared via solution casting method. The blend ratio of MKS and GLY was fixed at 1:1 wt. %, while the composition of oregano essential oil (OEO) was varied from 0, 0.3, 0.4, 0.5, and 0.6 wt. %. In this study, the effect of OEO on mechanical, morphological and biodegradable properties of MKS - GLY films were evaluated. From the analysis, the optimum tensile strength of MKS – GLY film was obtained at 1.10 MPa, while the addition of 0.4 wt. % OEO to MKS – GLY film resulted in optimum tensile properties, which give a smooth surface with less voids, as presented in the micrographs by scanning electron microscope (SEM). Moreover, the addition of 0.4 wt. % OEO to MKS – GLY film exhibited minimum weight loss during soil burial test, thus confirmed the function of OEO as an antimicrobial agent.